Peran Social Media Marketing dan Electronic Word of Mouth dalam Repurchase Intention pada Traveloka di Kota Bandung - Lestari, Atiqah Noor Amalia; Nurtjahjadi, Edi (Universitas Batanghari, 2024)
The objective of this research is to examine how Social Media Marketing and Electronic Word of Mouth influence Repurchase Intention via TikTok among Traveloka users in Bandung City. A quantitative approach with purposive sampling technique was employed in this study. The research sample consists of 90 respondents who meet specific criteria. The research population includes individuals who have used and transacted through the Traveloka application. Data were collected using questionnaires distributed online and analyzed with hypothesis testing, multiple linear regression, classical assumption tests, reliability tests, and validity tests. The findings indicate that both social media marketing and electronic word of mouth exert a notable impact on repurchase intention among Traveloka users, both individually and collectively.